Terapia oclusal con placas (1995)
ABSTRACT: Occlusal plates constitute alternative solutions to muscular and articular problems. When there are etiological factors in the muscular and articular disorders, occlusal plate is recomended to have a reversible and not invasive initial therapy. Then, it is extremely important to identify the cause-effect relationship before the irreversible theraphy starts.